2020
DOI: 10.3390/molecules25173966
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of Lipid-Soluble Bioactives by Nanoemulsions

Abstract: Lipid-soluble bioactives are important nutrients in foods. However, their addition in food formulations, is often limited by limited solubility and high tendency for oxidation. Lipid-soluble bioactives, such as vitamins A, E, D and K, carotenoids, polyunsaturated fatty acids (PUFA) and essential oils are generally dispersed in water-based solutions by homogenization. Among the different homogenization technologies available, nanoemulsions are one of the most promising. Accordingly, this review aims to summariz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 113 publications
(133 reference statements)
0
11
0
1
Order By: Relevance
“…Moreover, the particle sizes of bio-squalene nanoemulsion were 222 nm with Tween 20 and 230 nm with Biophilic H (Figure b), which were smaller than the particle sizes of the control nanoemulsions. These small particle sizes can influence the rheological, physical, and chemical properties of emulsions . Thus, the ζ potential and particle size parameters indicate that bio-squalene nanoemulsions may be useful for cosmetic purposes.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the particle sizes of bio-squalene nanoemulsion were 222 nm with Tween 20 and 230 nm with Biophilic H (Figure b), which were smaller than the particle sizes of the control nanoemulsions. These small particle sizes can influence the rheological, physical, and chemical properties of emulsions . Thus, the ζ potential and particle size parameters indicate that bio-squalene nanoemulsions may be useful for cosmetic purposes.…”
Section: Resultsmentioning
confidence: 99%
“…• Aceites esenciales (orégano, mandarina, limón, menta, eucalipto, tomillo, carvacrol, limoneno) • Ácidos grasos (atún, café, tomillo, menta, eucalipto, cacahuate) • Fenólicos (polifenoles, antocianinas, luteína, flavonoides, betacianina, betaxantina, taninos, carotenos, licopeno, tocoferol, curcumina, quercetina, catequina, resveratrol, propóleo, tangeretina, nobiletina, ácido gálico, Stevia) • Vitaminas (A, D, E, K) Micanquer-Carlosama et al, 2017;Jemaa et al, 2018;Pulit-Prociak et al, 2019;Mudric et al, 2019;Carpenter et al, 2019;Stasse et al, 2019;Suyanto et al, 2019;Banasaz et al, 2020;Basar et al, 2020;Medina-Pérez et al, 2020;Ozkan et al, 2020;Dammak et al, 2021;Paulo et al, 2021;Tessaro et al, 2022 LI • Aceites esenciales (mirceno, citral, linalol, oleorresina) • Ácidos grasos (palmítico, oleico, linoleico, esteárico, pescado, eucalipto) • Fenoles (polifenoles, antocianinas, carotenoides, flavonoides, betaninas, curcumina, propóleo, ácido gálico, ácido cumárico, oleuropeína, ácido ferúlico) Ballesteros et al, 2017;Marín et al, 2017;Yamashita et al, 2017;Nogueira et al, 2017;Enciso-Sáenz et al, 2018;Mangiring et al, 2018;Krisanti et al, 2019;Rezvankhah et al, 2019;Guo et al, 2020;Forstinus Nwabor et al, 2020;Baeza et al, 2020;Ogrodowska et al, 2020;González-Ortega et al, 2020;Pashazadeh et al, 2021;Jovanović et al, 2021;Bhagya Raj & Dash, 2022;…”
Section: Exunclassified
“…However, due to their poor water solubility, vulnerability to pollution, and low bioavailability, these lipophilic compounds often fail to perform their unique functions 1,2 . In recent years, studies have shown that nanoemulsions can embed lipid‐soluble active substances and improve their stability 3 . However, emulsion systems can be disrupted by the oil–water interface.…”
Section: Introductionmentioning
confidence: 99%